ANALISIS KURIKULUM PROGRAM STUDI ILMU PERPUSTAKAAN UIN SUNAN KALIJAGA YOGYAKARTA BERDASARKAN TREN TOPIK PENELITIAN TUGAS AKHIR MAHASISWA - Anwar, Ahmad; Zahra, Novi Sayidda (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
(Objectives) This research aims to explore trends in final assignment research topics among students of the Library Science Study Program at UIN Sunan Kalijaga Yogyakarta and compare them with the existing curriculum. (Method) The research approach applied is co-word analysis. Research data were obtained from keywords in the abstract section of the final assignments of the Library Science Study Program, which are stored in the institutional repository of UIN Sunan Kalijaga Yogyakarta, with a total of 353 theses. (Findings) The results show that topics such as libraries, school libraries, reading interest, information literacy, and digital libraries are strengths of the study program's research. Furthermore, based on cluster analysis, there is a consistent correlation between the research topics produced in the final assignments and the curriculum. However, it is worth considering the inclusion of topics such as film studies and semiotics in the study program curriculum.